Simulation of Solid Electrolyte Interphase Growth for Lithium Batteries Based on Kinetic Monte Carlo - Junfu Li; Xueli Hu; Tongxin Li (Energy Material Advances)
Lithium-ion batteries (LIBs) serve as the primary energy source for electric vehicles and smart devices. However, during the usage, the formation of the solid electrolyte interphase (SEI) film is closely related to the capacity decline of the battery, playing a crucial role in the battery performance and lifespan. This study focuses on the growth mechanism of SEI, revealing its evolution during the cycling process of charge and discharge, as well as its impact on the battery’s capacity retention and cycle stability. By establishing a simulation model based on the kinetic Monte Carlo (KMC) dynamics method, the dynamic growth process of the SEI on microsecond timescale under various discharge rates is simulated, achieving a quantitative prediction of SEI growth trends. The experimental part uses 18650 LIBs and validates the accuracy of the KMC model through constant current charge–discharge cycle aging experiments, with the simulation error within 4%. The results indicate that the growth rate of the SEI layer gradually increases during charging and decreases during discharging, with more SEI formed during charging than discharging at the same rate. As the number of aging cycles increases, the proportion of capacity loss caused by the SEI first decreases, then increases, and finally decreases again. This finding provides a new perspective for understanding the growth mechanism of the SEI.